The Utilization of Kepok Banana Fruit (Musa Paradisiaca, L.,) As An Alternative Media NA (Nutrient Agar) for the Growth Of Bacteria and Mushrooms - Marbun, Eva Diansari; S, Supartiningsih (Asian Journal of Pharmaceutical Research and Development, 2021)
The high cost of instant media such as nutrients encourages researchers to find alternative media from materials that are easily available and cheap. This study aims to determine the growth of bacteria and fungi in alternative media using different carbohydrate sources. The carbohydrate sources used were banana peel and kepok fruit and the results were compared with Nutrient agar (NA) media for bacterial growth and Potato Dextrose Agar (PDA) medium for fungal growth. This research was conducted experimentally. Kepok banana fruit is processed by cutting it into small pieces then mashed in a blender then filtered and deposited to get the starch, then dried in a drying cupboard at 40oC for 12 hours or until the texture is cracked and dry. The tested bacteria and fungi were inoculated by the scatter method and incubated at 37°C for 24 hours. The parameters observed were the number of bacterial and fungal colony populations. The mutant Streptococcuswas highest population of in the kepok banana starch medium with a concentration of 5%, Pseudomonas aeruginosa the highest population of was in the kepok banana starch medium with a concentration of 5% and Aspergillus niger the highest population of was in the kepok banana starch medium with a concentration of 5%. Based on the results of the research on the number of bacterial and fungal colonies, the best results were on the medium of 5% concentration of kepok banana starch. The results showed that the medium of kepok banana starch can be used as an alternative medium for the growth of bacteria and fungi, the most optimal medium is the medium of starch of kepok banana.